2008
DOI: 10.1111/j.1471-4159.2008.05289.x
|View full text |Cite
|
Sign up to set email alerts
|

Group III metabotropic glutamate receptor activation suppresses self‐replication of undifferentiated neocortical progenitor cells

Abstract: We evaluated the possible functional expression of metabotropic glutamate receptors (mGluRs) by neural progenitors from embryonic mouse neocortex. Constitutive expression was seen with group I, II, and III mGluRs in undifferentiated cells and neurospheres formed by clustered cells during culture with epidermal growth factor. The group III mGluR agonist, l‐2‐amino‐4‐phosphonobutyrate, drastically reduced proliferation activity at 1–100 μM without inducing cell death, with group I and group II mGluR agonists bei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

6
2

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 52 publications
0
24
0
Order By: Relevance
“…Activation of the GABA A R subtype could lead to the increased self-replication activity in neural progenitor cells along with the promotion of subsequent differentiation into astroglia (23,24), while activation of the GABA B R subtype would result in the similarly efficient promotion of self-renewal activity together with the facilitation of subsequent differentiation into neurons (31). On the other hand, activation of the NMDAR subtype could lead to the suppressed selfrenewal capacity along with the promotion of subsequent differentiation into neurons (57), while activation of the group III mGluR subtype would result in the similarly efficient suppression of self-renewal activity together with the facilitation of subsequent differentiation into astroglia (59). Therefore, modulation of the functionality of particular GABA and/or glutamate receptor subtypes would be of a great benefit for the regeneration and supplementation of neuronal and/or astroglial lineages without surgical implantations of neural progenitor cells in patients suffering from a variety of brain diseases relevant to neuronal and/or astroglial dysfunctions.…”
Section: Amino Acid Signaling To Neurogenesismentioning
confidence: 99%
See 1 more Smart Citation
“…Activation of the GABA A R subtype could lead to the increased self-replication activity in neural progenitor cells along with the promotion of subsequent differentiation into astroglia (23,24), while activation of the GABA B R subtype would result in the similarly efficient promotion of self-renewal activity together with the facilitation of subsequent differentiation into neurons (31). On the other hand, activation of the NMDAR subtype could lead to the suppressed selfrenewal capacity along with the promotion of subsequent differentiation into neurons (57), while activation of the group III mGluR subtype would result in the similarly efficient suppression of self-renewal activity together with the facilitation of subsequent differentiation into astroglia (59). Therefore, modulation of the functionality of particular GABA and/or glutamate receptor subtypes would be of a great benefit for the regeneration and supplementation of neuronal and/or astroglial lineages without surgical implantations of neural progenitor cells in patients suffering from a variety of brain diseases relevant to neuronal and/or astroglial dysfunctions.…”
Section: Amino Acid Signaling To Neurogenesismentioning
confidence: 99%
“…Therefore, we first examined the similarity of the murine embryonic carcinoma stem cell line P19 cells to murine neural progenitor cells (59). P19 cells cultured with ATRA within 4 days showed formation of neurospheres immunoreactive for nestin, but neither MAP2 nor GFAP.…”
Section: Cyclind1 Promoter Activitymentioning
confidence: 99%
“…extracellular glycine is effectively increased by blocking GLYT1 and that this mediates synaptic integration by dual activation of both the glycine receptor and the NMDA receptor [20,21]. Numerous previous studies have shown that proliferation of NPCs is regulated by activation of various receptors and these neurotransmitters; i.e., activation of the GABAA receptor, group I metabotropic glutamate (mGlu) receptor or dopamine D 3 receptor enhances proliferation of NPCs [22][23][24], whereas activation of the NMDA receptor, group III mGlu receptor, or α4β2 nicotinic acetylcholine receptor suppresses proliferative activity [25][26][27][28].…”
Section: Discussionmentioning
confidence: 99%
“…PCR reaction products were separated on 1.5% agarose gels with ethidium bromide for visualization. PCR conditions were as follows: GAPDH (denaturation at 94°C for 1 min, annealing at 60°C for 1 min, and extension at 72°C for 1 min; 24 cycles); MAP2 and neuron specific enolase (NSE) (denaturation at 94°C for 1 min, annealing at 65°C for 1 min, and extension at 72°C for 1 min; 25 cycles); GFAP, CD11b, and synaptotagmin-1 (denaturation at 94°C for 1 min, annealing at 65°C for 1 min, and extension at 72°C for 1 min; 26 cycles); GABA B R1 and GABA B R2 (denaturation at 94°C for 1 min, annealing at 65°C for 1 min, and extension at 72°C for 1 min; 27 cycles); Densitometry was done with the individual PCR products with a densitograph, followed by calculation of ratios of expression of mRNA for each set of primers over that for GAPDH (28). The relative abundance of each PCR product was determined by quantitative analysis of digital photographs of gels using Image J software (National institute of health, Bethesda, MD, USA).…”
Section: Rt-pcrmentioning
confidence: 99%
“…Whole brains and discrete brain structures dissected were individually homogenized in 20 mM Tris-HCl buffer (pH 7.5) containing 1 mM EDTA, 1 mM EGTA, 10 mM sodium fluoride, 10 mM sodium β-glycerophosphate, 10 mM sodium pyrophosphate, 1 mM sodium orthovanadate, and 1 μg/ml of various protease inhibitors [(pamidinophenyl)methanesulfonyl fluoride, leupeptin, antipain, and benzamidine], followed by centrifugation at 4°C for 5 min at 15,000 × g as described elsewhere (28). Pellets thus obtained were suspended in the 20 mM TrisHCl buffer (pH 7.5) mentioned above.…”
Section: Western Blottingmentioning
confidence: 99%